Genetic localisation of the RP2 type of X linked retinitis pigmentosa in a large kindred. Issue 7 (July 1991) - Wright, A F; Bhattacharya, S S; Aldred, M A; Jay, M; Carothers, A D; Thomas, N S; Bird, A C; Jay, B; Evans, H J
Abstract : Genetic linkage and deletion studies have led to the proposal that there are at least two loci on the X chromosome which are responsible for X linked retinitis pigmentosa (XLRP). One locus (RP3) has been closely defined by genetic linkage and deletion analyses and localised to the region between the ornithine transcarbamylase (OTC) and chronic granulomatous disease (CYBB) loci in Xp21.1-p11.4. The other locus (RP2) has been assigned by linkage analysis alone to region Xp11.4-p11.2, but its localisation is less well defined. The results of a multipoint linkage analysis of a single large XLRP kindred using eight informative loci provide further evidence on the localisation of RP2 to this region. The maximum likelihood location of this locus shows a multipoint lod score of 7.17 close to DXS255 (in Xp11.22) and TIMP (in Xp11.3-p11.23), neither of which show recombination with RP2, in an area extending from 2 cM proximal to DXS7 to 1 cM distal to DXS14 (approximate 95% confidence limits).